SUPPLEMENTARY ACTIVE OUTDOOR LEARNING PROCESS FOR CLASSROOM LEARNING: A META-SYNTHESIS STUDY - Yusuf SÖZER; Oral BEHÇET (International Journal of Eurasia Social Sciences, 2016)
The purpose of this study, is to assess the current situation of the supplementary outdoor learning process in Turkey Primary Schools by gathering the findings of inquiries via meta-synthesis method. Data of this study are derived from the 18 thesis and dissertatitions held between 2004-2014. Synthesis findings are represented below as: ? Teachers who conduct suplementary active outdoor learning activities mostly perform preparative activities before outdoor learning.? Pupils, find those preparative activities as helpful and beneficial.? The learning experience gained in outdoor learning places is expressed as effective by pupils and teachers. ? Acording to pupils’ and teachers’ view, active outdoor learning contributes to pupils’ cognitive and emotional development. In this context, it provides more meaningful, joyful and retentive learning experiences.? Reinforcing activities performed in classrooms after outdoor learning is insufficient according to pupils’ view, is average according to teachers’ view. Pupils, find it important and beneficial to support with reinforcing activities in classroom after outdoor learning activities.debates on abortion site nyc abortion clinics